Trade-offs in organic nutrient management strategies across mixed vegetable farms in Southwest British Columbia - Norgaard, Amy E.; Lewis, DeLisa; Borden, Kira A.; Krzic, Maja; Carrillo, Juli; Smukler, Sean M. (Frontiers in Sustainable Food Systems, 2022)
Balancing economic and environmental objectives can present trade-offs for organic farmers maximizing crop yields while maintaining core principles of ecology and health. A primary challenge for achieving this balance is nitrogen (N) and phosphorus (P) management. Meeting crop N requirements with compost can build soil carbon (C) and soil health but often over-applies P and increases soil P and associated environmental risks. Alternatively, high-N organic fertilizers can provide N without surplus P but can be expensive and lack C inputs that composts supply. We evaluated these potential trade-offs in two-year field trials on 20 mixed vegetable farms across three regions of southwest British Columbia, Canada, capturing a range of climatic-edaphic conditions and organic amendments. Three nutrient management strategies were evaluated: High Compost: compost applied to meet crop N removal, Low Compost + N: compost applied to meet crop P removal plus an organic fertilizer to meet crop N removal, and Typical: varying combinations of composts and/or organic fertilizers (‘typical’ nutrient application on the farm). Nutrient strategies were evaluated in terms of yield, input costs, and soil properties (permanganate oxidizable C (labile C responsive to soil management), and post- season available N and P). Soil P was 21% higher with High Compost than Low Compost + N. In one region characterized by inexpensive but nutrient-rich composts and soils high in P, input costs were lowest with Typical, but in the second year, High Compost outperformed Typical in crop yield. Principal component analysis showed a divergence in post-season NO3- between nutrient strategies in relation to compost and soil properties: High Compost using high-N composts increased post-season NO3- (0-30 cm), whereas relative yields in High Compost tended to be higher on farms with lower soil C and lower C:N composts, while yields with Typical were higher under opposite conditions but associated with higher post-season NO3-. Combining input types (e.g. Low Compost +N) can meet environmental objectives in reducing surplus soil P without short-term yield or cost trade-offs compared to High Compost. However, maintaining soil C needs to be investigated to achieve effective ecological nutrient management in organic vegetable production with improved nutrient balances.